Determination of free and total sulfites in wine using an automatic flow injection analysis system with voltammetric detection - Luis Moreira Goncalves (2010)
An automated flow injection analysis (FIA) system, based on an initial analyte separation by gas-diffusion and subsequent determination by square-wave voltammetry (SWV) in a flow cell, was developed for the determination of total and free sulfur dioxide (SO2) in wine. The proposed method was compared with two iodometric methodologies (the Ripper method and a simplified method commonly used by the wine industry). The developed method displayed good repeatability (RSD lower than 6%) and linearity (between 10 and 250 mg l-1) as well as a suitable LOD (3 mg l-1) and LOQ (9 mg l-1). A major advantage of this system is that SO2 is directly detected by flow SWV.